After Effects Compositing: 3 Advanced Matching and Looks. - Christiansen, Mark (linkedin.com, 2014)
Learn how to composite 3D and 2D elements, color correct footage, match an original shot's light and motion, and use HDR and filmic looks to create realistic, cinematic sequences.